Psychological well-being and value-semantic sphere of personality among psychology students - T. S. Pilishvili; A. I. Savushkina; A. L. Danilova; N. C. Soruko Torres (Russian State Vocational Pedagogical University, 2021)
Introduction. The relevance of the study of psychological well-being and its correlation with the value-semantic sphere of the personality among students-psychologists is due to the need to train specialists in helping professions, who are able to carry out competent psychological support of the subject during a period of growing instability.The aim of the present research is to identify the characteristics of psychological well-being and its correlations with the value-semantic sphere of psychology students' personality in terms of personal values, basic semantic attitudes, self-actualisation of the personality, a dynamic system of life meanings for understanding and working out flexible supra-professional skills associated with self-organisation and self-development of career paths to maintain professional health.Methodology and research methods. The theoretical and methodological basis of the study was the subject-activity approach to psychological well-being and the value-semantic sphere of the individual, developed by the Russian psychology, taking into account the scientific works of foreign authors. An empirical study was conducted among students-psychologists of the Peoples' Friendship University of Russia (N = 80) using the psychodiagnostic methods: "Scale of Psychological Well-Being" by K. Riff (adapted by T. P. Shevelenkova and P. P. Fesenko), "Self-Actualization Test" (by E. Shostrom), "Value Questionnaire" (by Sh. Schwartz), test "Meaningful Orientations" (by D. A. Leontiev), "System of Life Meanings" (by V. Yu. Kotlyakov), "Basic Semantic Attitudes" (by A. D. Ishkov and N. G. Milardova). The following methods of mathematical statistics were applied: correlation (Spearman's р) and factor analysis (principal component method), IBM SPSS Statistics 22 program.Results. The revealed significant correlations between psychological well-being, value orientations and semantic attitudes of psychology students confirm that the respondents' goal-setting is limited by the lack of a sense of independence, as well as the need to combine new and traditional methods for society to manage and control their activities. Self-actualisation of the individual is constrained by the presence of semantic attitudes of the respondents, reflecting their dependence on emotional support and the opinions of others. The results of factor analysis demonstrate the presence of five factors in the personality structure: the factor of safety and stability of life when it is meaningful and manageable; the factor of self-actualisation regardless of the environment; the factor of psychological well-being with the meaningfulness of personal development; the factor of manifesting concern for the well-being of loved ones with a decrease in exactingness and responsibility for them; the factor of achieving personal success with the ability to take risks.Scientific novelty. The authors made an attempt at investigating the correlations of psychological well-being with certain aspects of the value-semantic sphere of the personality among young specialists in the helping profession, for whom this area of the psyche acquires professional and personal significance.Practical significance. The results of the current research can be employed in the course of preparation and design of professional supervision programmes for students-psychologists, as well as in the process of development of over-professional skills associated with the reflection of young specialists of their own life-creating resources, located in the space of complex interaction of psychological well-being and value-semantic sphere.